Structure and Assembly of TP901-1 Virion Unveiled by Mutagenesis - Stockdale, Stephen R.; Collins, Barry; Spinelli, Silvia; Douillard, François P.; Mahony, Jennifer; Cambillau, Christian; van Sinderen, Douwe (PLOS ONE, 2015)
Bacteriophages of the Siphoviridae family represent the most abundant viral morphology in the biosphere, yet many molecular aspects of their virion structure, assembly and associated functions remain to be unveiled. In this study, we present a comprehensive mutational and molecular analysis of the temperate Lactococcus lactis-infecting phage TP901-1. Fourteen mutations located within the structural module of TP901-1 were created; twelve mutations were designed to prevent full length translation of putative proteins by non-sense mutations, while two additional mutations caused aberrant protein production. Electron microscopy and Western blot analysis of mutant virion preparations, as well as in vitro assembly of phage mutant combinations, revealed the essential nature of many of the corresponding gene products and provided information on their biological function(s). Based on the information obtained, we propose a functional and assembly model of the TP901-1 Siphoviridae virion.